2002
DOI: 10.1152/ajpgi.00331.2001
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin reduces colitis in rats via modulation of the immune system and correction of cytokine imbalance

Abstract: Natural immunomodulator lactoferrin is known to exert an anti-inflammatory effect. However, there have been no studies that examine the mode of action of lactoferrin in reducing intestinal damage. We investigated the effect of lactoferrin on a trinitrobenzenesulfonic acid (TNBS)-induced colitis model in rats. Bovine lactoferrin was given once daily through gavage, starting 3 days before (preventive mode) or just after TNBS administration (treatment mode) until death. The distal colon was removed to be examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 39 publications
6
68
2
Order By: Relevance
“…4). It is reported that BLF causes the down-regulation of TNF-α and IL-1β and the upregulation of IL-10 via inhibition of the nuclear factor-κB pathway, which is involved in the regulation of many inflammation-associated genes [24]. TNF-α increases in synovial tissue and synovial fluid [20] and plays a pivotal role in the pathology of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). It is reported that BLF causes the down-regulation of TNF-α and IL-1β and the upregulation of IL-10 via inhibition of the nuclear factor-κB pathway, which is involved in the regulation of many inflammation-associated genes [24]. TNF-α increases in synovial tissue and synovial fluid [20] and plays a pivotal role in the pathology of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous or intraperitoneal administration of LF reduces the production of TNF-α and IL-6 in vivo [13,26]. Oral administration of bovine milk-derived LF (BLF) also decreases TNF-α and IL-6 production [25] and increases IL-10 production [24] in vivo. In the mouse collagen-induced and septic arthritis models, periarticular injection of human LF reduces inflammation [9].…”
mentioning
confidence: 99%
“…6,9,15 In the case of apo-lactoferrin, it has potential as a new therapeutic agent for inflammatory bowel disease. 56 It is important to say that apo-lactoferrin affects pathogens such as Salmonella enterica serovar Typhimurium and E. coli without inhibiting the growth of bifidobacteria. These data suggest that lactoferrin may have the potential to be combined with probiotic bacteria in biotherapeutic products, which could help to balance human gut microflora and limit the overgrowth of certain pathogenic microorganisms, 57 including parasites.…”
Section: Amoebicidal Effect Of Human Milk Is Due To the Protein Fractmentioning
confidence: 99%
“…The mechanisms underlying the observed clinical improvement have not been fully elucidated but in cats it has been reported that, bovine lactoferrin can also reduce IFN-γ production by concanavalin A stimulated peripheral blood mononuclear cells [37]. Interestingly, related studies of intestinal inflammation in rats have also shown a clinical improvement following oral administration of bovine lactoferrin and this was associated with an enhanced production of IL-4 and IL-10 and a reduction in TNF-α, IL-1β and IL-6 [53].…”
Section: Mucosal Cytokines and The Response To Mucosal Infectionmentioning
confidence: 99%